Indomethacin solubility estimation in 1,4-dioxane + water mixtures by the extended hildebrand solubility approach (2023)
Extended Hildebrand Solubility Approach (EHSA) was successfully applied to evaluate the solubility of Indomethacin in 1,4-dioxane + water mixtures at 298.15 K. An acceptable correlation-performance of EHSA was found by using a regular polynomial model.